2021
DOI: 10.1021/acs.jafc.1c03852
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dissipation, Residue, and Risk Assessment of Diniconazole Enantiomers in Four Kinds of Fruits

Abstract: Chiral diniconazole is a widely used triazole fungicide, while its enantioselective behaviors in fruits have not been reported. In this article, the absolute configuration was confirmed. A fast supercritical fluid chromatography-tandem mass spectrometry (SFC-MS/MS) method was developed for the chiral separation and enantioselective study of diniconazole in four kinds of fruits. The residual concentrations gradually decreased with time in four kinds of fruits after applying diniconazole. The dissipation half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Enantioselectivities can occur in various agricultural products, which may be the same or different. S -Diniconazole showed faster degradation than R -diniconazole in four kinds of fruits (apple, pear, jujube, and peach) . (−)- R -zoxamide was preferentially degraded in tomato, an opposite preference was found in pepper and grape, and no enantioselectivity was observed in cucumber …”
Section: Cultivation Processmentioning
confidence: 96%
See 1 more Smart Citation
“…Enantioselectivities can occur in various agricultural products, which may be the same or different. S -Diniconazole showed faster degradation than R -diniconazole in four kinds of fruits (apple, pear, jujube, and peach) . (−)- R -zoxamide was preferentially degraded in tomato, an opposite preference was found in pepper and grape, and no enantioselectivity was observed in cucumber …”
Section: Cultivation Processmentioning
confidence: 96%
“…S-Diniconazole showed faster degradation than R-diniconazole in four kinds of fruits (apple, pear, jujube, and peach). 123 (−)-R-zoxamide was preferentially degraded in tomato, an opposite preference was found in pepper and grape, and no enantioselectivity was observed in cucumber. 124 S-(+)-Mandipropamid degraded more rapidly than the R-(−)-mandipropamid in tomato and Chinese cabbage, whereas reversed preference was found in cucumber and cowpea.…”
Section: ■ Cultivation Processmentioning
confidence: 99%
“…Based on the supercritical fluid chromatographytandem mass spectrometry method, S-diniconazole was preferentially degraded in fruits. 13 The bioactivity of Smandipropamid was 118−592 times greater than that of Rmandipropamid against six plant pathogens. 14 S-Triticonazole had greater acute toxicity to non-target aquatic and terrestrial organisms.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Many studies have reported a stereoselective phenomenon of chiral fungicides in environmental media and organisms. Based on the supercritical fluid chromatography-tandem mass spectrometry method, S -diniconazole was preferentially degraded in fruits . The bioactivity of S -mandipropamid was 118–592 times greater than that of R -mandipropamid against six plant pathogens …”
Section: Introductionmentioning
confidence: 99%
“…In agricultural production, pesticides are widely used to control pathogenic bacteria, pests, and weeds to ensure high crop quality and yield and play a vital role in the development of human civilization. 1 As a new class of systematic fungicides developed in the past few years, succinate dehydrogenase inhibitors (SDHIs) can inhibit a wide variety of plant phytopathogenic fungi and have been widely used in biological control. 2 SDHI-type fungicides have attracted increasing attention because of their unique structure, high activity, and broad fungicidal spectrum.…”
Section: Introductionmentioning
confidence: 99%